The brain developing memory in developing brains, birth to five years - Halula, Wes; Halula, Jenica; Learning Zone Express (Firm) (United State : Learning Zone Express, 2010)
The human brain is fascinating - every movement we make, conscious or unconscious, stems from our brains. The most critical time for brain development is from birth to age five. What can parents and caregivers of children do to help give those developing brains the best chance for success? Discover how the basic workings of the brain influence our memory and how we learn and what can be done to encourage healthy.
Executive Producer, Melanie Nelson ; camera, Wes Halula.
Hosted by Corey Mills.
DVD format.
Keywords: Brain; Brain -- Growth